Description of a new species of the genus Insect 1936, Evans Austroagallia from the family Paperglove in Iraq (Journal of the College of Basic Education, 2022)
The study presents a description of a new type of paper glove, genus 1936 Austroagallia Evans, where the study clarified some of the characteristics of this genus. Penis and ligament, genital plate, pen, genitalia, male abdominal base, and the shape of the female urethra, which includes the middle and lower valves of the egg-laying machine, and the seventh abdominal sternum.